Menelusuri Jejak Pemelihara Al-Qur’an Studi Kasus Pondok Pesantren Tahfiz KH Harun Nafsi, Samarinda - al-Haqiri, Muhammad Syatibi (SUHUF, 2009)
Indonesia is a country which most its populations are Moslems. The tradition of learning the holy QurÃ¢â‚¬â„¢an by heart was begun since the development of Islam in this country. There are many methods to learn the holy QurÃ¢â‚¬â„¢an by heart. One of the methods isÃ‚Â  through the pesantren (traditional Islamic boarding school) for learning the holy QurÃ¢â‚¬â„¢an by heart orÃ‚Â  tahfÃ„Â«z. Harun Nafsi`s pesantren educates the huffÃ„Âz (those who learn the QurÃ¢â‚¬â„¢an by heart). This pesantren also has a great role to increase QurÃ¢â‚¬â„¢anic education in East Kalimantan, especially to prepare the huffaz of the QurÃ¢â‚¬â„¢an for joining in the National Competition of Recitation of the Holy QurÃ¢â‚¬â„¢an (MTQ), to be imam of the mosque, and other purposes.Ã‚Â  The tahfiz`s methodsÃ‚Â  are readingÃ‚Â  (qirÃ„ÂÃ¢â‚¬â„¢ah), depositing some QurÃ¢â‚¬â„¢anic verses the students have learnt by heartÃ‚Â  (setoran),Ã‚Â  learning by heart and repeating what have been learnt by heartÃ‚Â  (takrÃ„Â«r). TheÃ‚Â  qiraÃ¢â‚¬â„¢ah that KH Masruni used is known as qiraÃ¢â‚¬â„¢ah of Imam Ã¢â‚¬â„¢Asim through Imam Hafs, and his chains (sanad) from KH Muhammad Munawwir, Krapyak, Yogyakarta